2017
DOI: 10.1108/ijmpb-12-2015-0114
|View full text |Cite
|
Sign up to set email alerts
|

A robust algorithm for project portfolio selection problem using real options valuation

Abstract: Purpose The principal concern of organization managers in the global rivalry of commerce environment is how to select the project portfolio among available projects. In this matter, organizations should consider the uncertainty intrinsic in the projects regarding an appropriate valuation technique within an optimization framework. In this research, the purpose of this paper is to formulate using a robust optimization algorithm to deal with the complexities and uncertainty inherent in the construction of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The resulting model was solved using a robust combinatorial algorithm. The results showed that project details can have a deep impact on even the simplest selection of project portfolio under uncertainty [24]. Qu et al (2017) formulated the problem of multi-objective portfolio optimization with the objective of reducing investment risk and increasing stock return.…”
mentioning
confidence: 99%
“…The resulting model was solved using a robust combinatorial algorithm. The results showed that project details can have a deep impact on even the simplest selection of project portfolio under uncertainty [24]. Qu et al (2017) formulated the problem of multi-objective portfolio optimization with the objective of reducing investment risk and increasing stock return.…”
mentioning
confidence: 99%
“…The values of all these weights range from zero to one. The next step after determining the network weights is to obtain a set of predictions (Y), compare them with their counterparts among real observations (O), and measure the difference in terms of the mean squared error [16], which is presented in Eq. (3).…”
Section: A Prediction Network Optimizationmentioning
confidence: 99%
“…Therefore, we will save the first three best solutions and force other search agents (omegas) to update their position according to the position of the best search agents based on Eqs. (10)(11)(12)(13)(14)(15)(16).…”
Section: Detecting the Position Of The Preymentioning
confidence: 99%
See 1 more Smart Citation
“…In all these studies the notion of uncertainty is partly conflated with that of risk of project failure, or inversely, probability of success (PoS). However, several studies introduce measures of uncertainty that capture variance of R&D portfolio performance more broadly, such as: Value at Risk (VaR) or Conditional Value at Risk (CVaR) [34], fuzzy value [43], reward/loss ratios [38,44,46] or value probability thresholds [34,38,40,[44][45][46]48,49], variance of portfolio value distribution [39,42,44,50,51], semivariance below or above portfolio value thresholds [42], or covariance of portfolio value, cumulative probability distribution of portfolio value and Gini criteria [41]. A final set of methods emerging from the health economic literature attempt to measure the impact of this variance on the probability that a portfolio is chosen [42,52,53].…”
Section: Introductionmentioning
confidence: 99%